GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 49512 species occurrences available in GBIF matching the query: TaxonKey: Stercorarius pomarinus (Temminck, 1815) HasGeospatialIssue: false HasCoordinate: true. The dataset includes 49512 records from 109 constituent datasets: 23 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 19 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 43 records from OEH Atlas of NSW Wildlife. 13 records from Australian National Wildlife Collection provider for OZCAM. 2 records from QLD DERM Coastal Bird Atlas (Trial). 6 records from Bird Atlas 2007 - 2011. 34 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 64 records from PlutoF platform observations. 2 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 1 records from The avian collection at the Natural History Museum, Oslo, Norway. 76 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 32 records from Southern African Bird Atlas Project. 3 records from Merseyside BioBank - North Merseyside Birds (verified). 45 records from DMNS Bird Collection (Arctos). 22 records from Clare Biological Records Centre dataset. 10 records from Fauna Atlas N.T.. 9108 records from Artdata. 12 records from Museum Victoria provider for OZCAM. 1 records from Eggs Specimen. 18 records from SA Fauna (BDBSA). 1 records from Lund Museum of Zoology (MZLU). 85 records from Historical Bird Atlas. 31 records from UAM Bird Collection (Arctos). 1 records from CCBER Ornithology Collection. 403 records from BirdLife Australia, Birdata. 38 records from Museum of Comparative Zoology, Harvard University. 5 records from SEAPOP NINA. 175 records from CAS Ornithology (ORN). 27846 records from EOD - eBird Observation Dataset. 76 records from iNaturalist Research-grade Observations. 1 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 5 records from NYSM Birds. 40 records from NMNH occurrence DwC-A. 2 records from Cruzando el Caribe - Construyendo la capacidad para el ecoturismo en el Darién y Urabá. 61 records from naturgucker. 1 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 97 records from First Bird Atlas. 6 records from SBMNH Vertebrate Zoology. 27 records from LACM Vertebrate Collection. 5 records from Western Australian Museum provider for OZCAM. 3 records from Macaulay Library Audio and Video Collection. 1 records from Watervogels - Wintering waterbirds in Flanders, Belgium. 2 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 8 records from RBINS collections. 1 records from Birds of Ireland. 1 records from Collection Ornithologie - SNSD. 5 records from Great Backyard Bird Count. 1 records from BC Coastal Waterbird Survey. 44 records from Canadian Museum of Nature Bird Collection. 33 records from UWBM Ornithology Collection. 607 records from PIROP (Shipboard Surveys). 5 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 3807 records from SEAMAP - marine mammals, birds and turtles. 1 records from Bay of Fundy Species List (OBIS Canada). 2 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 8 records from Royal British Columbia Museum. 3 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 296 records from North West Territories and Nunavut Bird Checklist, Canada. 1 records from Paleobiology Database. 1 records from NBM birds. 1 records from Birds Specimens. 43 records from SDNHM Birds Collection. 21 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 2 records from Biologiezentrum Linz. 37 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 9 records from UCLA Donald R. Dickey Bird and Mammal Collection. 131 records from Naturalis Biodiversity Center (NL) - Aves. 1 records from ANTXXIII-8 Birds and Mammals. 71 records from WFVZ Bird Collections. 5 records from PSM Vertebrates Collection. 2 records from MLZ Bird Collection (Arctos). 3 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 2 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 3 records from Abundance of birds in the Lena Delta Region. 1 records from Abundance of birds on the channels of Lena Delta in the fall migration period. 1489 records from DOF. 1 records from WIWO (NL) - Monitoring and breeding ecology of arctic birds at Medusa Bay. 1 records from ANTXXIII-8 Birds and Mammals (SCAR-MarBIN: Antarctic OBIS). 198 records from DOF 2001-2006. 2 records from AMNH Bird Collection. 8 records from DATAVES. 2 records from MVZ Egg and Nest Collection (Arctos). 22 records from Ornitho.eus. 33 records from Bird Specimens. 2 records from Queensland Museum provider for OZCAM. 1 records from CM Birds Collection. 1 records from Birds fallen at Danish Lighthouses 1883 through 1939. 5 records from Geographically tagged INSDC sequences. 2921 records from Norwegian Species Observation Service. 4 records from MSB Host Collection (Arctos). 5 records from USGS ASC - Changing Arctic Ecosystems - Birdlist - 2011-2013. 2 records from Bernice P. Bishop Museum. 4 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7 records from Cowan Tetrapod Collection - Birds. 2 records from Staffordshire Ecological Record - SER Species-based Surveys. 36 records from UMMZ Birds Collection. 2 records from DMNH Birds. 51 records from EBCC Atlas of European Breeding Birds. 1 records from Queen Victoria Museum Art Gallery provider for OZCAM. 1 records from National System of Protected Areas in Poland - Animals. 1 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 177 records from MVZ Bird Collection (Arctos). 6 records from KUBI Ornithology Collection. 730 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 1 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 15 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 174 records from European Seabirds at Sea (ESAS) bird sightings from 1980 to 2003.. 2 records from CUMV Bird Collection (Arctos). 3 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups.
Keywords: GBIF; biodiversity; species occurrences